Extracting the time‐dependent resonances of a vehicle–bridge interacting system by wavelet synchrosqueezed transform. Issue 12 (2nd September 2021) - Mostafa, Neda; Di Maio, Dario; Loendersloot, Richard; Tinga, Tiedo
Abstract: The dynamic response of a vehicle–bridge interaction (VBI) system is a noisy, nonstationary, and multicomponent response with closely spaced spectral components. Considering the ultimate goal as utilizing the VBI system instantaneous frequencies (IFs) for bridge condition monitoring, this paper carries out a systematic study to investigate the performance of four advanced time‐frequency analysis techniques on a series of VBI responses: Hilbert–Huang transformation (HHT), continuous wavelet transform (CWT), robust local mean decomposition (robust‐LMD), and wavelet synchrosqueezed transform (WSST). The novel contribution of this study is the application of the two latter techniques. The synthesized tests demonstrate that the WSST is the best method to precisely separate and localize in time the closely spaced resonances. Therefore, the WSST is applied to field measurements obtained from the Boyne viaduct in Ireland, as well. The results verify the capacity of this method to deal with time‐varying vibrations adequately.